2021
DOI: 10.1212/wnl.0000000000011107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diffusion Mismatch to Select Pediatric Patients for Embolectomy 6 to 24 Hours After Stroke

Abstract: ObjectiveTo determine whether thrombectomy is safe in children up to 24 hours after onset of symptoms when selected by mismatch between clinical deficit and infarct.MethodsA secondary analysis of the Save ChildS Study (01/2000–12/2018) was performed, including all pediatric patients (<18 years), diagnosed with Arterial Ischemic Stroke who underwent endovascular recanalization at 27 European and United States stroke centers. Patients were included if they had a relevant mismatch between clinical deficit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
1
16
0
1
Order By: Relevance
“…The outcome in this case report is in line with the findings of a secondary analysis of the Save ChildS Study that included 20 patients aged <18 who had thrombectomy between 6 and 24 h after stroke onset based on mismatch between clinical deficit and infarct (6). In the cited study by Sporns et al, the authors reported a higher proportion of good outcomes as compared to the DAWN and DEFUSE3 studies, and a similar proportion of patients with good outcome in the group treated > 6 h as compared to the group treated < 6 h (6).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The outcome in this case report is in line with the findings of a secondary analysis of the Save ChildS Study that included 20 patients aged <18 who had thrombectomy between 6 and 24 h after stroke onset based on mismatch between clinical deficit and infarct (6). In the cited study by Sporns et al, the authors reported a higher proportion of good outcomes as compared to the DAWN and DEFUSE3 studies, and a similar proportion of patients with good outcome in the group treated > 6 h as compared to the group treated < 6 h (6).…”
Section: Discussionsupporting
confidence: 73%
“…As for delay, two randomized trials in adults (DAWN and DEFUSE 3) demonstrated that the delay from stroke onset to thrombectomy can be extended beyond the usual 6-h window in patients who present a mismatch between the severity of the clinical deficit and the infarct volume, or between the infarct volume and the perfusion deficit (4,5). Also, a secondary analysis of the Save Child study, which focused on thrombectomy performed between 6 and 24 h based on the presence of a mismatch between clinical deficit and infarct in 20 patients aged <18, revealed a good functional outcome in these patients (6).…”
Section: Introductionmentioning
confidence: 99%
“…For mechanical thrombectomy (MT) in adults, several randomized clinical trials published in 2015 have shown the efficacy and safety of endovascular recanalization for large vessel occlusions (LVOs) with large effect size (8). In children, after several case series (9, 10), the retrospective Save ChildS Study recently provided the first systematic evidence for the safety of MT in children (11)(12)(13). In this study, the rate of recanalization and adverse events was comparable to large randomized controlled trials in adults, and neurological outcomes of the children were generally favorable.…”
Section: Introductionmentioning
confidence: 99%
“… 63 67 However, a secondary analysis of the Save ChildS study has recently shown that thrombectomy in an extended time window of up to 24 h after onset of symptoms was safe and neurological outcomes were generally good, if patients were selected by a mismatch between clinical deficit and infarct. 68 The 2019 AHA guidelines were written before this evidence became available. 69 We therefore recommend to perform EVT in pediatric patients with LVO even in the extended time window beyond 6 h after symptom onset.…”
Section: Borderline Indications For Evtmentioning
confidence: 99%